Efektivitas Kinerja Kantor Urusan Agama Pattallassang Dalam Pelayanan Bimbingan Manasik Haji bagi Calon Jamaah Haji di Kecamatan Pattallassang - Arbiadi, Muh. Aidil; Arifin, Nurul Ainun; Dhiya’uddin Alim, Abdul Fathin; Anggraeni, Nurliana; Ihsan, Muh.; A, Anita; Nurislamia, St. Atika (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the effectiveness of the performance of the Religious Affairs Office (KUA) in providing hajj manasik guidance services to prospective hajj pilgrims. KUA has an important role as an institution that provides initial guidance to prospective pilgrims before departure to the holy land. The research method used is qualitative with a case study approach at one of the KUA in a certain area. Data were collected through observation, interviews, and documentation. The results of the study indicate that in general, KUA has carried out its manasik guidance function quite effectively, marked by the implementation of routine manasik activities, the availability of relevant materials, and active participation from prospective pilgrims. However, there are several obstacles such as limited human resources, facilities, and time allocation that still need to be improved. Therefore, stronger synergy is needed between KUA, the Ministry of Religion, and the community to improve the quality of hajj manasik guidance services in order to achieve independent and sharia-compliant hajj implementation.